Sustainability and Contemporary Society - Barquero Cabrero, José Daniel; Medina Elizondo, Manuel (Opción, 2016)
Contemporary human societies face with perplexity and lack of fundamental solutions challenges represented by current sustainability crisis, in the context of increasing economic and social inequalities in despite of the expansion and deepening of market logic on a global scale, unprecedented in humankind history. That has challenged not only our perceptions about the benefits of economic growth and capitalism, but also about the capacity of planet to absorb damage inflicted by humankind “ecological footprint”.